2020
DOI: 10.1186/s12974-020-01932-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of astrocyte-derived IL-33 in neonatal hypoxic-ischemic brain injury

Abstract: Background: Interleukin-33 (IL-33) is a well-recognized pleiotropic cytokine which plays crucial roles in immune regulation and inflammatory responses. Recent studies suggest that IL-33 and its receptor ST2 are involved in the pathogenesis of neurological diseases. Here, we explore the effect of IL-33/ST2 signaling in neonatal hypoxicischemic (HI) brain injury and elucidate the underlying mechanisms of action. Methods: The brain HI model was established in neonatal C57BL/6 mice by left common carotid artery oc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 43 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…Several post-mortem and preclinical studies have highlighted the importance of astrocytes and their potential interactions with MG [ 60 , 61 ]. These include a study that demonstrated using transgenic, and pharmacologic approaches in vivo and in vitro that astrocyte derived IL33 is an endogenous neuroprotective agent in a mouse more of NE including by HI including by supporting the M2-like phenotype of MG [ 132 ]. In an EoP model, the existence of a tripartite glial circuits has been demonstrated: the OPC maturation blockade by MG activation required an astrocytic reactivity, via an overproduction of cyclo-oxygenase-2 (COX)-2 [ 133 ].…”
Section: Microglia and Other Cellular Brain Partnersmentioning
confidence: 99%
“…Several post-mortem and preclinical studies have highlighted the importance of astrocytes and their potential interactions with MG [ 60 , 61 ]. These include a study that demonstrated using transgenic, and pharmacologic approaches in vivo and in vitro that astrocyte derived IL33 is an endogenous neuroprotective agent in a mouse more of NE including by HI including by supporting the M2-like phenotype of MG [ 132 ]. In an EoP model, the existence of a tripartite glial circuits has been demonstrated: the OPC maturation blockade by MG activation required an astrocytic reactivity, via an overproduction of cyclo-oxygenase-2 (COX)-2 [ 133 ].…”
Section: Microglia and Other Cellular Brain Partnersmentioning
confidence: 99%
“…ST2 or IL-33 deficiency exacerbates ischemic brain injury after MCAO in mice (60,61). Conversely, exogenous IL-33 treatment protects mice against experimental ischemic stroke (9, 63-65) and neonatal hypoxic ischemic brain injury (62). Mechanistically, IL-33 does not directly act on neurons.…”
Section: Il-33 In Ischemic Strokementioning
confidence: 99%
“…In the mouse model of ischemic stroke induced by middle cerebral artery occlusion (MCAO), IL-33 mRNA and protein expression are obviously upregulated in lesions, and mature oligodendrocytes and astrocytes are responsible for this upregulation (9,(60)(61)(62).…”
Section: Il-33 In Ischemic Strokementioning
confidence: 99%
“…IL-10 released from astrocytes suppressed neuronal apoptosis in response to HIE via the TLR2/NFκB pathway in a rat model of hypoxia-ischemia [ 114 ]. Similarly, the astrocyte-derived IL-33 following HIE is upregulated in the first 24 h post-HIE, and the ST2 receptor, the receptor for IL-33, was shown to be upregulated in astrocytes post-HIE [ 115 ]. Importantly, exogenous delivery of IL-33 via intraperitoneal injection alleviated the resultant brain injury 7 days post-HIE.…”
Section: Contributions Of Central and Peripheral Cells To Neonatalmentioning
confidence: 99%